GESTION DE TALENTO HUMANO EN LA EMPRESA JARQUIFAR DE LA CIUDAD DE DURAN - Urrutia Goyes, Dagoberto Eduardo (2018)
CIA LTDA, its offices are located in Duran km 6 ½, it is a company Cuencana, born in the 90s, as an initiative of a family group, with presence in the national pharmaceutical market and aimed at improving its procedures. Is a work option for several families at the country level and a reference of quality, as well as an alternative treatment for several health situations of the Ecuadorian family. The same that in its organic and functional structure contemplates the following levels of activities: a) Executives, represented by the General Shareholders' Meeting. At this level you it is up to the determination of their policies and strategies; monitoring compliance with objectives and goals, through the officials and officials of the Executive Level. B) Executive, represented by the General Management; Areas and Production Managements. At this level you It is the responsibility of formulating the programs and action plans to implement the policies and guidelines given by the Shareholders' Meeting and to coordinate in general the activities, supervising and controlling compliance with them. And c) Operational, represented by the different departments, operating units, agencies and business units. At this level It is responsible for the execution of programs, projects and activities of the company.